Impact of queuosine modification of endogenous E. coli tRNAs on sense codon reassignment - Tittle, Jillyn M.; Schwark, David G.; Biddle, Wil; Schmitt, Margaret A.; Fisk, John D. (Frontiers in Molecular Biosciences, 2022)
The extent to which alteration of endogenous tRNA modifications may be exploited to improve genetic code expansion efforts has not been broadly investigated. Modifications of tRNAs are strongly conserved evolutionarily, but the vast majority of E. coli tRNA modifications are not essential. We identified queuosine (Q), a non-essential, hypermodified guanosine nucleoside found in position 34 of the anticodons of four E. coli tRNAs as a modification that could potentially be utilized to improve sense codon reassignment. One suggested purpose of queuosine modification is to reduce the preference of tRNAs with guanosine (G) at position 34 of the anticodon for decoding cytosine (C) ending codons over uridine (U) ending codons. We hypothesized that introduced orthogonal translation machinery with adenine (A) at position 34 would reassign U-ending codons more effectively in queuosine-deficient E. coli. We evaluated the ability of introduced orthogonal tRNAs with AUN anticodons to reassign three of the four U-ending codons normally decoded by Q34 endogenous tRNAs: histidine CAU, asparagine AAU, and aspartic acid GAU in the presence and absence of queuosine modification. We found that sense codon reassignment efficiencies in queuosine-deficient strains are slightly improved at Asn AAU, equivalent at His CAU, and less efficient at Asp GAU codons. Utilization of orthogonal pair-directed sense codon reassignment to evaluate competition events that do not occur in the standard genetic code suggests that tRNAs with inosine (I, 6-deaminated A) at position 34 compete much more favorably against G34 tRNAs than Q34 tRNAs. Continued evaluation of sense codon reassignment following targeted alterations to endogenous tRNA modifications has the potential to shed new light on the web of interactions that combine to preserve the fidelity of the genetic code as well as identify opportunities for exploitation in systems with expanded genetic codes.